INFLUENCE OF VARIETAL PROPERTIES ON GRAIN YIELD AND QUALITY OF WINTER WHEAT - Марініч, Любов; Тоцький, Віктор; Шостя, Анатолій; Кузьменко, Лариса; Ільченко, Марія (SWorldJournal, 2024)
Topicality. Wheat is the main cereal crop in world trade with an average production volume of 720–760 million tons. In addition, the issue is not only increasing the yield, but also improving the quality indicators of the grain. Therefore, improving grain